Optimal Allocation of Water Resources in Irrigation Areas Considering Irrigation Return Flow and Uncertainty - Feilong Jie; Liangjun Fei; Youliang Peng; Sheng Li; Yanyan Ge (Applied Sciences)
To improve the utilization rate of water resources in irrigation areas, this study established an uncertain water resource optimal allocation model considering the reuse of return flow, and it analyzed the impact of return flow reuse on irrigation efficiency, crop planting structure, and water resource allocation in irrigation areas. If only the optimal allocation of irrigation diversion is carried out, the net profit for the current years, short-term (2021–2040) planning years, and long-term (2041–2060) planning years will increase by USD [18.27, 24.18], [2.20, 2.47], and [3.02, 3.43] million, respectively, and the total planting area in the current years, short-term planning years, and long-term planning years will increase by 900 ha, 700 ha, and 1000 ha, respectively. Restricted by the total amount of irrigation water diversion, the irrigation water resources in the current years and the planning years are in deficit. When the channel return flow is optimized, the net profit of the current years and the short-term and long-term planning years will increase by USD [7.14, 7.97], [5.08, 5.63], and [4.4, 4.81] million, respectively. The total planting area in the current years and short-term and long-term planning years will increase by 2.6, 1.9, and 1.6 thousand ha, respectively, and the amount of irrigation water diversion will decrease by [12, 18], [18, 24], and [20, 26] million m3, respectively. Reasonable and optimized use of channel return flow can not only improve the irrigation efficiency of irrigation areas and avoid the impact of return flow discharge on the water quality of the Yellow River, but it can also reduce the cost of water extraction and save water resources.